Uphill walking at iso-efficiency speeds - Milic, Mirjana (Biol Sport, 2020)
Uphill walking gait has been extensively studied, but the optimal uphill speed able to enhance the metabolic demand without increasing fatigability has so far received little attention. Therefore, the aim of this study was to assess the metabolic/kinematic demand at constant speed (6 km·h(−1) G0 level, G2 2% uphill, G7 7% uphill) and at iso-efficiency speeds (G2IES 5.2 km·h(−1) 2% uphill and G7IES 3.9 km·h(−1) 7% uphill). For this aim, physically active women (n:24, Age 33.40 ± 4.97 years, BMI 21.62 ± 2.06 kg/m(-2)) after an 8-min warm-up were studied on a treadmill for 10ʹ for every walking condition with a 5ʹ rest in between. Average heart rate (AVG-HR), rating of perceived exertion (RPE) and kinematic variables (stance time, swing time, stride length, stride cycle, stride-length variability, stride-cycle variability and internal work) were studied. Modifications in stance time, stride length and stride cycle (p<0.005), and lower internal-work values (p<0.001) occurred in G7IES in comparison to the other conditions. Swing time was significantly modified only in G7IES compared to G0 and G7 (p<0.001 and p<0.005, respectively). Stride-length variability and stride-cycle variability were higher in G7IES compared to the other conditions (p<0.001). G7 induced the highest AVG-HR (p<0.005) and RPE (p<0.001) compared to the other conditions. This study demonstrates that by applying the equation for uphill walking gait, it is possible to maintain a similar metabolic demand and RPE at iso-efficiency speeds during uphill compared to level walking, inducing at the same time a modification of the kinematic parameters of walking gait performed at the same slope condition.